Optimization of the Emitting Coil of a Hardware-Software Complex for Study of Low-Frequency Electromagnetic Radiation’s Shielding Effectiveness - O. D. Kanafyev; A. V. Trukhanov; T. I. Zubar; S. A. Chizhik; S. S. Grabchikov (Приборы и методы измерений)
Optimization of the radiation coil of the hardware-software complex for studying the effectiveness of shielding of low-frequency electromagnetic radiation will make it possible to assess the effectiveness of shielding coatings at a higher level. This fact will make it possible to develop coatings with improved characteristics. The purpose of this work was to determine the optimal characteristics of the emitting coil which will ensure its stable operation and magnetic field strength in the frequency range up to 100 kHz.The parameters of the manufactured samples, such as inductance (L), active (R) and total resistance (Z), were obtained using an MNIPI E7-20 emittance meter. In practice, the coils with the optimal parameters calculated theoretically were connected to a current source and amplifier. To detect electromagnetic radiation, a multilayer inductor connected to a UTB-TREND 722-050-5 oscilloscope was used as a signal receiver.The results of measurements showed that the resistance of multilayer coils is approximately 1000 times higher than that of single-layer coils. Also, for multilayer coils, an avalanche-like increase in total resistance is observed starting from a frequency of 10 kHz, while for single-layer coils there is a uniform increase in total resistance over the entire frequency range up to 100 kHz.The paper presents results of research on the correlation of the performance of single-layer and multilayer inductors depending on their parameters in the frequency range from  20 Hz  to  100 kHz. Values of the voltage required to provide the magnetic field strength of 1, 5, 20 Oe at 25 Hz and 100 kHz have been calculated. After analyzing the data obtained, the optimal parameters of the inductor were found which ensure stable performance in the frequency range up to 100 kHz.